CONCEPTUAL ANALYSIS OF ORGANIZATIONAL COMMUNICATION IN IMPROVING COORDINATION, WORKING RELATIONS, AND ORGANIZATIONAL EFFECTIVENESS - Annisa Ariftha; Nursapia Harahap (Program Pascasarjana UIN Sumatera Utara, 2026)
Organizational communication is a fundamental element in building coordination, working relationships, and the effectiveness of achieving organizational goals. This article aims to conceptually examine the meaning, function, media, forms, and flow of organizational communication in supporting the work dynamics of modern organizations. This study uses a qualitative approach based on literature review by examining various relevant concepts and theories of organizational communication. The results of the study indicate that organizational communication functions not only as a process of conveying messages, but also as a mechanism for integration, control, coordination, decision-making, and the formation of interpersonal relationships. Effective communication enables each member of the organization to clearly understand their roles, duties, and responsibilities. In addition, the use of appropriate communication media, whether interpersonal media, group media, or digital technology-based media, can accelerate the distribution of information and reduce the potential for misunderstandings. Verbal and nonverbal forms of communication also play an important role in strengthening the meaning of the message conveyed. Meanwhile, the flow of vertical, horizontal, internal, and external communication shows that organizations require an open, directed, and continuous communication system. This article emphasizes that organizational success is greatly influenced by the ability to manage messages, communication networks, relationships between members, and responses to a dynamic environment. Thus, organizational communication can be understood as the primary foundation for creating an organization that is adaptive, productive, and oriented toward achieving shared goals.